PENGGUNAAN PENDEKATAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Siti, Nursiti Fatimah; Aprinawati, Iis; Fadhilaturrahmi, Fadhilaturrahmi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study is to improve the learning outcomes of students of grade V SD Negeri 016 Bangkinang Kota through learning by applying realistic mathematical approach. This is done to improve the learning conditions undertaken. The study was conducted using classroom action research with 27 subjects, 13 male students and 14 female students. The instrument used in this study is a learning tool, to measure students' ability in each cycle used test questions. Technique of data analysis in this research is done quantitatively by processing data of teacher and student activity and also data of understanding result of learning from test. While qualitative data are analyzed to supplement quantitative data. Based on the results of action, it can be said that learning with realistic mathematics approach can improve the learning outcomes of students of grade V SD Negeri 016 Bangkinang Kota.